Unlocking the power of AI in CRM: A comprehensive multidimensional exploration - Khadija Khamis Alnofeli; Shahriar Akter; Venkata Yanamandram (Journal of Innovation & Knowledge)
Artificial intelligence (AI) is revolutionising customer relationship management (CRM) across various sectors, fundamentally altering strategic business operations. This study examines the capabilities of AI-powered CRM systems, drawing on empirical evidence arising from thematic analyses of 64 scholarly articles and insights gained from 24 in-depth interviews with CRM experts. The research identifies and systematically categorises three major dimensions and eight sub-dimensions of AI-powered CRM capabilities, providing a structured framework that encapsulates the complex interplay that occurs between these elements. These dimensions include data management, multi-channel integration, and tailored service offerings, each underpinning the nuanced integration of AI into CRM practices. Critically, the study integrates these findings within the theoretical framework of the microfoundations of Dynamic Capabilities (DC), enriching the discourse on how AI can strategically enhance CRM systems and offering a nuanced understanding of the factors driving AI adoption within CRM. By mapping these capabilities against the microfoundations of DC theory, the research delineates the strategic implications for organisations striving to leverage AI to enhance their competitive advantage.